Kontrola pevnosti kostry kapoty diesel elektrické lokomotivy - Tomek, Petr; Paščenko, Petr; Středová, Doubravka (Univerzita Pardubice, 2012)
The original structural design of hood is analyzed in this paper. The whole construction is loaded by force caused by the weight of the structure. The parts of the hood are subject to the standards for railway applications CSN EN 12663-1 [1]. Numerical analyses are performed by FEM computer program COSMOSWorks [2]. The main aim of this paper is to determine critical points of construction on the basis of the results of numerical analyses.
Keywords: hood; railway applications; numerical analyses